Informe n° 38 - SITUACIÓN FITOSANITARIA - Región Centro Norte de Córdoba 08 de febrero de 2017 - Plazas, M. C.; Guerra, F.; Lábaque, M.; Vuletic, E.; Brücher, E; Guerra, G.D. (Informe de Situación Fitosanitaria, 2018)
Ninguno